PENGARUH ZAKAT PRODUKTIF DALAM PENINGKATAN INDEKS PEMBANGUNAN MANUSIA (IPM) - Yumsinah, Siti; Sanusi; Muflihah, Hani (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2024)
This research is motivated by productive zakat funds programmed by BAZNAS which have the aim of making the community more prosperous and also have a continuous income. Not in the form of funds given for temporary consumption needs, but the need to produce until finally mustahik becomes muzakki. Capital is given to be developed and become a source of livelihood. With this productive zakat, if managed properly and correctly, it will help the community's economy and also increase economic growth. The formulation of this research problem is: 1) Is there a change in mustahik income before and after receiving productive Zakat at Baznas Kota Serang Banten? 2) How is the effect of productive zakat on HDI in Baznas Kota Serang Banten? This research is a field research The type of research that the author uses is field research, namely research that seeks data directly to the field, In this study the numbers obtained from the questionnaire results were then processed into quantitative data using SPSS 22. Based on the research conducted, it can be explained that: 1) The researcher concluded that there was a change in the income received by the mustahiks before and after receiving productive zakat fund assistance. Previously, respondents were housewives (IRT) where they had no previous income. After receiving productive zakat funds, there is an increase in income generated. So it can be concluded that the rejection of H0 (there is no change in mustahik income before and after receiving zakat at Baznas Kota Serang Banten) and the acceptance of H1 (there is a change in mustahik income before and after receiving zakat at Baznas Kota Serang Banten). 2) Productive zakat has no influence on the Human Development Index (HDI), with a calculated t value of 0.891 with sig. t of 0.379 (p>0.05), so the decision accepts H0 and rejects H1. For this reason, it can be concluded that the productive Zakat variable has no effect on the Human Development Index (HDI) in Baznas Serang City Banten.